FOTO MAKANAN SEBAGAI MEDIA KONSELING KONVENSIONAL UNTUK MENINGKATKAN PENGETAHUAN SIKAP DAN PERILAKU DIET PASIEN DAN KELUARGA PASIEN DIABETES MELITUS RAWAT INAP DI RUMAH SAKIT PANCARAN KASIH MANADO - Rivolta G. M. Walalangi; Nonce N. Legi (POLTEKKES KEMENKES MANADO, 2017)
Photographs of foodstuffs is one of the counseling medium that can be used to facilitate the patient understand because the photos of the ingredients are equipped with the weight of the mature food ingredient (gram). And on some ingredients there is a dimension (length or width). In addition to the weight of the listed ingredients there is also the composition of macro nutrients such as: Calories, Carbohydrates, Proteins, FatsThis research type is Quasy Experiment pre and Post Test Control group This research design will describe difference of attitude and behavior attitude of diabetes mellitus patient in hospitalization beside that this research will describe ease and efficiency of nutrition counseling in patient of diabetes mellitus.The result of statistic test about the level of knowledge about diabetes mellitus obtained p value <0,05 (p = 0,000), meaning there is very significant difference of knowledge value about diabetes mellitus before and after counseling activity. Similarly attitudes and behavior of patients showed an increase with the value of p <0.05 (p = 0.00). This also shows a very significant difference in behavior before and after counseling using food photos. Conclusion there is difference of knowledge level, attitude and behavior of respondent after nutrition counseling using photo of food.